1977
DOI: 10.1051/rnd:19770808
|View full text |Cite
|
Sign up to set email alerts
|

Temporal fluctuations of plasma LH and testosterone in Charolais bull calves during the first year of life

Abstract: Some of these discrepancies could be due in part to a pulsatile pattern of relaese which has been described for LH both in adult (Katongole, Naftolin and Short, 1971) and young bulls (Gombe et al., 1973 ;Thibier, 1975). They could arise also from insufficient blood samplings or number of animals studied.This confusing situation in the bull contrasts with our knowledge in the sheep in which the prepubertal period is associated with a pulsatile pattern of LH followed by a decrease in the level after puberty, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
28
0
2

Year Published

1979
1979
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 9 publications
8
28
0
2
Order By: Relevance
“…LH was measured in all plasma samples from the same occasion, by radioimmunoassay, as previously described (Thibier, 1975a). Details of the radioimmunoassay of testosterone have also been reported previously (Thibier 1976a (Thibier, 19756, 1976a), but nevertheless these results are in total agreement with independent previous studies either from numerous animals per age group (Thibier, 1977) or from a few bulls submitted to regular blood sampling (Lacroix et al, 1977). It (Mongkonpunya et al, 1975 ;Lacroix et al, 1977 ;Thibier, 1976Thibier, , 1977 this elevation seems more rapid in the young animals than in the older ones.…”
supporting
confidence: 81%
“…LH was measured in all plasma samples from the same occasion, by radioimmunoassay, as previously described (Thibier, 1975a). Details of the radioimmunoassay of testosterone have also been reported previously (Thibier 1976a (Thibier, 19756, 1976a), but nevertheless these results are in total agreement with independent previous studies either from numerous animals per age group (Thibier, 1977) or from a few bulls submitted to regular blood sampling (Lacroix et al, 1977). It (Mongkonpunya et al, 1975 ;Lacroix et al, 1977 ;Thibier, 1976Thibier, , 1977 this elevation seems more rapid in the young animals than in the older ones.…”
supporting
confidence: 81%
“…This pattern was independent of season. Studies using other breeds of Bas taurus bulls (Rawlings et al 1972;Secchiari et al 1976;Lacroix et al 1977) were in general agreement but suggested that the timing of the pubertal trough may vary with breeds or conditions of management. Under the conditions existing at this laboratory, other studies (T. B.…”
Section: Discussionmentioning
confidence: 71%
“…(1) Remain unchanged with age (Karg et al 1976); (2) Be elevated with large fluctuations from 1 to 5 months of age and then to decrease and remain steady up to 1 year (Lacroix et al 1977); (3) Be biphasic with broad peaks extending from 2 to 5 months and from 11 to 12 months with an intervening trough (Rawlings et al 1972); (4) Increase linearly from 7 to 13 months of age (Lunstra et al 1978); and (5) Increase from birth to 3 months of age, decrease to a nadir at 8 months, and then rise over the next 4 months (Schams et al 1981). Our own LH results based on fewer ages of sampling tend to agree with the patterns reported by Rawlings et al (1972) and Schams et al (1981).…”
Section: Discussionmentioning
confidence: 99%
“…Erkek çiftlik hayvanlarından boğa (Lacroix et al 1977), koç (Lee et al 1976, Schanbecher ve Ford 1976, Olster ve Foster 1986 …”
Section: Materyal Ve Yöntemunclassified
“…AraĢtırmada, erkek Ankara keçisi oğlaklarında Mayıs ayında (ortalama iki aylık yaĢta) saptanan testosteron hormonu düzeyinin, eĢeysel olgunluk döneminin baĢlangıcından hemen önceki dönem olan Ağustos ayına (ortalama 5.5 aylık yaĢta) yaklaĢıldıkça önemli (P<0.01) ölçüde yükselme göstermesi, erkek buzağı (Lacroix et al 1977), erkek kuzularda (Lincoln 1976, Lee et al 1976, Schanbecher ve Ford 1976, Olster ve Foster 1986, erkek domuz (Colenbrander et al 1977) ve erkek oğlaklarda (Muduuli et al 1979, Mehta et al 1987, Chakraborty et al 1989, Ahmad et al 1996 elde edilen bulgular ile benzerlik göstermektedir.…”
Section: Materyal Ve Yöntemunclassified